204k views
1 vote
Let f(x) = (6x^3 – 7)^3 and g(x) = 6x^3 - 7.
Given that f(x) = (hog)(x), find h(x).

User Cquillen
by
5.2k points

2 Answers

4 votes

Answer:

h(x) = x³

Explanation:


\text{We can notice:}


g(x)=6x^3-7,\ f(x)=(\underbrace{6x^3-7}_(g(x)))^3=\bigg(g(x)\bigg)^3


\text{If}\ f(x)=(h\circ g)(x)=h\bigg(g(x)\bigg),\ \text{then}\ h(x)=x^3

User Lakshman Battini
by
4.7k points
5 votes

Answer:

h(x) = x^3.

Explanation:

h(x) = x^3

because (h o g)(x) = (6x^3 - 7)^3.

User Joe Glover
by
5.4k points